Draft Annual Plan 1987-88 Scheme Details Volume - II Government of Manipur - Planning Commission (Planning Commission, 1987)
Based on the experience of blanket allocation of 500 farming families irrespective of hills & valley one V.E.W., for the last 5 years, the necessity of reducing the number of farming families in the Hill districts is felt needed to compensate the loss of efficiency on the part of functionaries due to transport bottleneck and sparsely located villages.
Government of Manipur, State Planning Department